2008
DOI: 10.1135/cccc20080001
|View full text |Cite
|
Sign up to set email alerts
|

New Hydrophobicity Constants of Substituents in Pyrazine Rings Derived from RP-HPLC Study

Abstract: Pyrazine derivatives show a wide range of biological activities. 1-Pyrazin-2-ylethan-1-ones have served as food flavourants, and together with pyrazine-2-carbonitriles have been widely used as intermediates in the synthesis of various heterocyclic compounds. In our laboratory, substituted pyrazine-2-carbonitriles and 1-pyrazin-2-ylethan-1-ones have been used as intermediates for the preparation of potential antifungal and antimycobacterial drugs. Using established methods, a library of pyrazine derivatives was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…The obtained results of cytotoxicity correlate with the log k and Clog P parameters calculated in the work of Pospisilova et al [25]-the higher values of log k and Clog P parameters are, the higher IC 50 values are, for example, compound 6 (log k = 0.4859, IC 50 = 11.60 µM) >>>> compound 10 (log k = 0.6821, IC 50 = 6.28 µM) >> compound 11 (log k = 0.8155, IC 50 = 2.43 µM) ≈ compound 13 (log k = 0.9814, IC 50 = 2.17 µM). Naturally, these observations correspond with distributive parameters π (see Table 3), a constant characterizing hydrophobicity (lipophilicity contribution) of individual moieties, substituents, and substructures in some skeleton [31,32]; compound 6 (π Ar = 2.73) >>>> compound 10 (π Ar = 2.77) >> compound 11 (π Ar = 2.90) ≈ compound 13 (π Ar = 3.98). Nevertheless, di-substitution with highly lipophilic and electron-withdrawing substituents (Cl or CF 3 ) on the C (3,5) or C (3,4) positions of the anilide ring seems to be the most important for achieving a high antiproliferative effect.…”
Section: In Vitro Cell Viability Assaymentioning
confidence: 64%
“…The obtained results of cytotoxicity correlate with the log k and Clog P parameters calculated in the work of Pospisilova et al [25]-the higher values of log k and Clog P parameters are, the higher IC 50 values are, for example, compound 6 (log k = 0.4859, IC 50 = 11.60 µM) >>>> compound 10 (log k = 0.6821, IC 50 = 6.28 µM) >> compound 11 (log k = 0.8155, IC 50 = 2.43 µM) ≈ compound 13 (log k = 0.9814, IC 50 = 2.17 µM). Naturally, these observations correspond with distributive parameters π (see Table 3), a constant characterizing hydrophobicity (lipophilicity contribution) of individual moieties, substituents, and substructures in some skeleton [31,32]; compound 6 (π Ar = 2.73) >>>> compound 10 (π Ar = 2.77) >> compound 11 (π Ar = 2.90) ≈ compound 13 (π Ar = 3.98). Nevertheless, di-substitution with highly lipophilic and electron-withdrawing substituents (Cl or CF 3 ) on the C (3,5) or C (3,4) positions of the anilide ring seems to be the most important for achieving a high antiproliferative effect.…”
Section: In Vitro Cell Viability Assaymentioning
confidence: 64%
“…Described (2E)-N-phenyl-3-phenylprop-2-enamide (1) was characterized recently by Pospisilova et al [10]. (2E)-3-Phenyl-N- (3,4,5-trichlorophenyl)prop-2-enamide (5). Yield 75%; Mp 247.9 °C; IR (cm −1 ): 3157,3080,1655,1613,1583,1513,1433,1378,1337,1281,1245,1196,1188,1148,1011,998,967,944,880,860,815,762,711,685,617,602,575,536…”
Section: Synthesismentioning
confidence: 99%
“…Therefore, reversed-phase high performance liquid chromatography (RP-HPLC) methods have become popular and widely used for lipophilicity measurement. A general procedure is the measurement of directly accessible retention time under isocratic conditions with varying amounts of an organic modifier in the mobile phase using end-capped non-polar C18 stationary RP columns and calculating the capacity factor k [4][5][6][7][8][9]. Log k, calculated from the capacity factor k, is used as the lipophilicity index converted to log P scale [4].…”
Section: Introductionmentioning
confidence: 99%
“…Since it was found that the lipophilicity of these significantly biologically effective agents determined their activity, in this study hydrolipophilic properties of all three series are investigated. Thus this contribution is a follow-up work to the previous papers [5][6][7][8][15][16][17][18][19][20][21][22][23][24][25] aimed at the physicochemical properties of new biologically active agents.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reversed-phase high performance liquid chromatography (RP-HPLC) methods have become popular and widely used for lipophilicity measurement. A general procedure is the measurement of directly accessible retention time under isocratic conditions with varying amounts of an organic modifier in the mobile phase using end-capped non-polar C 18 stationary RP columns and calculating the capacity factor k [4][5][6][7][8]. Log k, calculated from the capacity factor k, is used as the lipophilicity index converted to log P scale [4].…”
Section: Introductionmentioning
confidence: 99%